Collaborative Online International Learning (COIL) for Critical Reading of Media: Collaboration between IIUM and Kansai University - Shiozaki, Hiroko (Kulliyyah of Languages and Management, International Islamic University Malaysia, 2016)
This paper is aimed to discuss the possibility of Collaborative Online International Learning (COIL) to develop skills and critical attitudes toward mass and social media. COIL is a “new paradigm” of online learning that involves classes from more than two countries in order to promote intercultural competence. While COIL has great potential in solving problems of international/ intercultural misunderstanding, it is still less known in Malaysia and the Muslim world. This study is an action research on the presenter’s educational activities in the course of “Introduction to International Communication”. Both qualitative and quantitative data are collected through the two COIL projects between Kansai University (KU) and International Islamic University Malaysia (IIUM). The first COIL was conducted from March to May 2015 and the main theme was cultural stereotype in mass media. The second was from September to December 2015 with a different course in KU and the main theme was the problems and possibilities of social media. The students’ response shows that collaboration with students in other country gives positive impact on their cultural awareness and critical viewpoint toward media. These experience led students to reflect the characteristics of own society, culture and media usage. Such reflective view point is essential for critical reading of information provided by mass media and internet. Even though the projects requires continuous improvement, the possibility of COIL is not limited to cultural competence but also includes the media literacy in general.